Riset Pasar Konsumen Terhadap Makanan Tradisional Kota Pontianak - Hidayah, Nurul (Jurnal TIN Universitas Tanjungpura, 2019)
Traditional food is a feature of cultural diversity in Indonesia. Traditional food also functions as the identity of each region, including Pontianak City. This research was conducted to produce a level of consumer market tastes towards traditional Pontianak City food, resulting in a consumer classification and producing the main factors that determine the consumer market tastes of traditional Pontianak City food. Obtaining data in this study is based on observations in the field, and the results of distributing questionnaires addressed to respondents. This research processes data using the SPSS 20 process, which is the calculation of the number of samples, description of the respondent's character, validity test, and reliability test. The sample collection uses the Slovin formula calculation by assuming the confidence level up to 90%, then the e value is obtained = 100% - 90% = 10% or 0.1. Consumer classification of traditional Pontianak City food, namely age 41.41% age 40 years and over, gender 73.74% female, income 70.71% under 1 million rupiah, education 54.55% high school, employment 49.50% IRT, and regional origin 65.66% Kota Pontianak. The main factors that determine the tastes of the Pontianak City traditional food consumer market are factors due to hunger, factors due to distinctive and delicious taste, presentation or display factors, affordable traditional food price factors, guaranteed traditional food hygiene factors, factors due to health and nutrition, factors because of diverse foods, factors due to food uniqueness, factors due to pride, factors due to feeling healthy, factors due to quality, factors due to trends, factors due to healthy lifestyles, factors due to natural concepts, factors due to practical and simple factors due to knowing health benefits, quality factors. The total number of statement results of the research questionnaire, namely very agree score 441, agree score 759, doubtful score 249, disagree score 173, and strongly disagree score 61. Keywords: Market Taste Level, Consumer Classification, Key Determinants Traditional food is a feature of cultural diversity in Indonesia. Traditional food also functions as the identity of each region, including Pontianak City. This research was conducted to produce a level of consumer market tastes towards traditional Pontianak City food, resulting in a consumer classification and producing the main factors that determine the consumer market tastes of traditional Pontianak City food. Obtaining data in this study is based on observations in the field, and the results of distributing questionnaires addressed to respondents. This research processes data using the SPSS 20 process, which is the calculation of the number of samples, description of the respondent's character, validity test, and reliability test. The sample collection uses the Slovin formula calculation by assuming the confidence level up to 90%, then the e value is obtained = 100% - 90% = 10% or 0.1. Consumer classification of traditional Pontianak City food, namely age 41.41% age 40 years and over, gender 73.74% female, income 70.71% under 1 million rupiah, education 54.55% high school, employment 49.50% IRT, and regional origin 65.66% Kota Pontianak. The main factors that determine the tastes of the Pontianak City traditional food consumer market are factors due to hunger, factors due to distinctive and delicious taste, presentation or display factors, affordable traditional food price factors, guaranteed traditional food hygiene factors, factors due to health and nutrition, factors because of diverse foods, factors due to food uniqueness, factors due to pride, factors due to feeling healthy, factors due to quality, factors due to trends, factors due to healthy lifestyles, factors due to natural concepts, factors due to practical and simple factors due to knowing health benefits, quality factors. The total number of statement results of the research questionnaire, namely very agree score 441, agree score 759, doubtful score 249, disagree score 173, and strongly disagree score 61. Keywords: Market Taste Level, Consumer Classification, Key Determinants